NURSING CARE FOR SOCIAL ISOLATION: WITHDRAWAL IN Mr. S WITH A FOCUS ON SOCIALIZATION THERAPY AT DR. RM. SOEDJARWADI KLATEN REGIONAL PSYCHIATRIC HOSPITAL - Anggita Presti Utami; Sudiarto; Wiwik Priyatin (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Background: Social isolation is a condition in which individuals feel lonely. This condition is often caused by a lack of interaction with others and reflects a negative and threatening situation. Therefore, nursing interventions are needed to reduce symptoms of social isolation and increase the interest in initiating interactions, one of which is through introduction training. Introduction training is an activity designed to develop an individual’s ability to initiate and maintain conversations, as well as to get to know others with the aim of building positive social relationships. Objective: This study aims to describe nursing care for social isolation disorder: withdrawal, with a focus on the intervention of introduction training. Method: This study used a descriptive method with a case study approach. Results: After three days of nursing interventions, the symptoms of social isolation: withdrawal were reduced, and the patient was able to introduce himself. Conclusion: Nursing care for social isolation: withdrawal, focusing on the introduction training intervention over three days, proved to be highly effective for patients with social isolation: withdrawal and can help reduce the associated symptoms.